2020
DOI: 10.1177/0300060520949762
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress regulates cell injury in lipopolysaccharide-induced nerve cells

Abstract: Objective Sepsis-associated encephalopathy (SAE) is a common complication of sepsis, and excessive endoplasmic reticulum (ER) stress is closely correlated with the cell injury caused by sepsis. This study aimed to analyze the possible role of ER stress in SAE cell models. Methods PC12 and MES23.5 cells were treated with increasing concentrations of lipopolysaccharides (LPS). The Cell Counting Kit-8 assay was used to detect cell viability and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Besides, it is reported that calpain is involved in regulating the activity of Caspase 3 and its upstream molecules Caspase 12 and Caspase 9 34 . ER stress mediates the apoptosis of most cells 7,10,12 . In our study, we demonstrated that LPS and CLP treatments markedly induced ER stress in CD4 + T cells within the appropriate time, as proved by the up‐regulated expression of ER stress markers, including p‐PERK/p‐eIF2α, IRE‐1α, ATF6, ATF4, XBP‐1 s, GRP78, CHOP, p‐JNK, calpain‐1, calpain‐2.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Besides, it is reported that calpain is involved in regulating the activity of Caspase 3 and its upstream molecules Caspase 12 and Caspase 9 34 . ER stress mediates the apoptosis of most cells 7,10,12 . In our study, we demonstrated that LPS and CLP treatments markedly induced ER stress in CD4 + T cells within the appropriate time, as proved by the up‐regulated expression of ER stress markers, including p‐PERK/p‐eIF2α, IRE‐1α, ATF6, ATF4, XBP‐1 s, GRP78, CHOP, p‐JNK, calpain‐1, calpain‐2.…”
Section: Discussionsupporting
confidence: 57%
“…Activated ER stress markers are responsible for transmitting signals to cell death through different mechanisms. The first is the activation of transcription factor CHOP mediated by PERK, IRE1, and ATF6, which has been reported to promote apoptosis protein Bax and inhibit anti‐apoptosis protein Bcl2 10 . The second is the activation of JNK mediated by the IRE1 pathway, which induces apoptosis by regulating apoptotic proteins such as Bcl2 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to secreting inflammatory cytokines [ 116 ], astrocytes also affect the release of neurotransmitters, which at last leads to neuronal injury [ 117 ]. Sepsis can dysfunction the autophagy and pyroptosis homeostasis [ 118 ] and activate ferroptosis [ 119 ] and endoplasmic reticulum stress of neurons, all of which could lead to neuronal damage [ 120 ]. Abnormal activation of neuronal membrane receptors can transmit stimulus signals and induce PANoptosis [ 121 ].…”
Section: Pathogenesismentioning
confidence: 99%